Peran Moderasi Green Concern dan Environment Knowledge Pada Pengaruh antara Greenwashing Perception Terhadap Green Purchase Intention - Siti Badiatul Umroh; Sutarmin .; Rizky Amalia (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
This research explores the influence of greenwashing, environmental knowledge, and green awareness on consumers’ intentions to buy eco-friendly products, while also assessing whether environmental knowledge and green awareness function as moderating variables. Employing a quantitative design, the study gathered data through a survey of 100 Coca-Cola consumers selected using purposive sampling. SmartPLS was used to examine validity, reliability, and the relationships among the constructs. The results indicate that greenwashing does not have a significant impact on green purchase intention, whereas environmental knowledge and green awareness show a positive and significant effect. The analysis also reveals that green awareness moderates the relationship between greenwashing and green purchase intention, while environmental knowledge does not demonstrate a meaningful moderating effect. In general, the study highlights the importance of consumers’ environmental understanding and awareness in supporting sustainable consumption and stresses the need for greater transparency in green marketing practices.